Educational Technology and Mentality After the Pandemic - Munthe, Yesyurun; Pramana, Agung (Pusat Riset dan Inovasi Nasional, 2024)
This study investigates the psychological effects of the pandemic on university students, particularly the persistence of psychological disorders and changes at the university level. The objective is to determine the extent of the impact of psychological changes on students. The research methodology involved conducting interviews with relevant parties to identify strategies for managing the disruptions that arose. The study revealed that psychological disorders, which can contribute to a lack of motivation for learning, decreased after implementing a learning approach that emphasizes exploring individual talents and interests. This approach also incorporates techniques to reduce psychological stress for each student